Global perspectives on educational leadership reform the development and preparation of leaders of learning and learners of leadership - Normore, Anthony H. (Bingley, U.K. : Emerald, 2010)
The interdependent relationship of leadership and learning for both academics and practitioners is critical for creating innovative leadership practices and partnerships needed for the 21st century schools. Due to the high pressure to demonstrate improvements in student achievement, leadership practices have increasingly resorted to conservative and prescriptive approaches focused more on increasing student achievement scores and less on the artistry of teaching and leading. This book is organized into three sections with four chapters in each section. Section One focuses on the socialization and professional development processes intended to prepare and develop prospective and practicing educational leaders into leadership positions; Section Two examines cultural, political, legal, economic, and social justice issues that affect leaders while serving in the role of educational leader/learner; Section Three encourages "interdisciplinary" educational leaders to re-examine who they are as leaders of learning, as learners of leadership, and life-long learners.
Connecting 'up there' with 'down here' : thoughts on globalisation, neo-liberalism and leadership praxis / Howard Stevenson and Autumn Tooms -- Building the leaders we need : the role of presence, learning conditions, and andragogy in developing leaders who can change the face of public pre-K through 12 education / Julie Slayton and Jonathan Mathis -- The new principal preparation program model in Israel : ponderings about practice-oriented principal training / Izhar Oplatka and Duncan Waite -- Development of university education in R.D. Congo : is a shift in policy making possible to implement the perspective of lifelong-learning? / Gaston Kapuku Mudipanu -- Free to become : the essence of learning and leading / Christopher Branson -- Development and preparation of leaders of learning and learners of leadership / Anthony H. Normore and Gaetane Jean-Marie -- Policies and paradox : a view of school leadership in the context of aboriginal education in Ontario, Canada / Lorenzo Cherubini and Louis Volante -- Poipoia kia puawai : a project to explore growth into leadership and cultural appropriacy in pre-service teacher education / Para Kana and Viv Aitkin -- Developing school leaders in times of radical change : investigating the school improvement zone of a large urban school district in United States / Anthony H. Normore and Mary V. Alfred -- Leading pedagogy : promoting school reform through teacher leadership and the implementation of a culturally-responsive pedagogy of relations / Mere Berryman, Suzanne SooHoo and Paul Wohler -- Leadership for inclusive schools and inclusive school leadership / Ann Nevin and Cristina Devecchi -- Zero-tolerance policies and the best interest of the students : making the case for restorative justice-based school discipline reform / Hollie Macky and Jacqueline A. Stefkovich -- Leaders transforming learning and learners : an Australian innovation in leadership, learning and moral purpose / Michael Bezzina and Charles Burford -- Fostering community-based learning leadership : a Korea-Zambia project design / Lynn Ilon and Costantine Malama -- An international collaboration : examining graduate educational leadership in Louisiana and Ontario / Pauline E. Leonard and Heather M. Rintoul -- Building adult educational programs in entrepreneurship based on Mezirow : the case of agricultural entrepreneurship / George S. Spais -- Leading upstream : professional learning for middle leaders / Allan Walker and Terrence Quong -- The changing face of purpose-driven school administration : green school leadership / Carly Ackley and Paul T. Begley -- Leading inquiry-based schools in a knowledge society / Meta Kruger.
Includes index.
Keywords: Education -- Administration -- General; Education -- Leadership; Organization & management of education; School management and organization; Educational leadership